Lead clinical and preclinical antimalarial drugs can significantly reduce sporozoite transmission to vertebrate populations. - Upton, L; Brock, P; Churcher, T; Ghani, A; Gething, P; Delves, M; Sala, K; Leroy, D; Sinden, R; Blagborough, A (2015)
To achieve malarial elimination, we must employ interventions that reduce the exposure of human populations to infectious mosquitoes. To this end, numerous antimalarial drugs are under assessment in a variety of transmission-blocking assays which fail to measure the single crucial criteria of a successful intervention, namely impact on case incidence within a vertebrate population (reduction in reproductive number/effect size). Consequently, any reduction in new infections due to drug treatment (and how this may be influenced by differing transmission settings) is not currently examined, limiting the translation of any findings. We describe the use of a laboratory population model to assess how individual antimalarial drugs can impact the number of secondary Plasmodium berghei infections over a cycle of transmission. We examine the impact of multiple clinical and preclinical drugs on both insect and vertebrate populations at multiple transmission settings. Both primaquine (>6 mg/kg of body weight) and NITD609 (8.1 mg/kg) have significant impacts across multiple transmission settings, but artemether and lumefantrine (57 and 11.8 mg/kg), OZ439 (6.5 mg/kg), and primaquine (<1.25 mg/kg) demonstrated potent efficacy only at lower-transmission settings. While directly demonstrating the impact of antimalarial drug treatment on vertebrate populations, we additionally calculate effect size for each treatment, allowing for head-to-head comparison of the potential impact of individual drugs within epidemiologically relevant settings, supporting their usage within elimination campaigns.